Comparison of the Use of Blender and Sketchup Applications in 3d Animation (Case Study: PT Rico Putra Selatan - Fitri Adinda; Agung Kharisma Hidayah; Dandi Sunardi; Muntahanah Muntahanah (Jurnal Komputer, Informasi dan Teknologi, 2022)
This study discusses the comparative analysis of the use of Blender and Sketchup Applications in 3D Animation (Case Study: PT Rico Putra Selatan), the comparison analyzed is the process of how long the rendering process takes using the Blender and Sketchup applications and how the quality of the visuals/images produced by Blender and Sketchup applications. However, this requires intensive resources and strong hardware to run, then the 3D animated video created will be used as a medium for promotion.Comparative analysis of Blender and Sketchup will result in testing the rendering speed, and image quality of the results of making 3D animated videos. The results of this study are able to state that Blender outperforms Sketchup in the comparison of rendering speed, and the image quality of this 3D animation video that Blender is superior to Sketchup.